Domniemania faktyczne i reguły dowodu prima facie: [Presumptions and prima facie evidence] (Studia Prawnicze / The Legal Studies, 2023)
This article discusses the function of presumptions and prima facie evidence in evidence proceedings. The discussion concentrates mainly on civil procedure but the Author considers also the possibility of applying presumptions in criminal proceedings. In part I, basic methodological issues connected with presumptions and prima facie evidence as well as with their application in judicial practice are shortly presented. The most important among them concerns the fact that there exist various interpretations of the above terms although generally they are not taken into account by the organs making decisions or by the representatives of the legal doctrine. In part II and III the Author presents commony known concepts of presumptions and prima facie evidence stressing their role in judicial proceedings and the influence on burdon of proof. On the basis of the above considerations in part IV the Author gives his own interpretation of the discussed institutions — the interpretation which seems to him the most operative as far as civil proceedings are concerned. In the Author’s opinion the structure of proof resulting from a presumption or from prima facie evidence is basicly identical. Its comparison with the structure of other legal evidence and especially with circumstantial evidence shows in what sense presumptions and prima facie evidence facilitate the evidence proceedings. On the other hand these rules differ as far as their influence on burdon of proof is concerned and this difference makes the scope of their application distinct. The possibility to introduce a presumption depends upon the non-existence of the hypotheses concurrent to the conclusions drawn from them, that is to say, exclusively upon praxeological considerations, while in case of prima facie evidence its introduction must be justified by axiological arguments discussed in this article (as e.g. the need of protecting the weaker party in the proceedings). Distinct conditions of application of these rules justify the suggestions made in legal theory and practice to treat them separately.